An Exploratory Study of Self-Consciousness and Emotion-Regulation Strategies in Health Care Workers. Issue 1 (August 2014) - Andela, Marie; Auzoult, Laurent; Truchot, Didier
The goal of this study was to assess relations between public self-consciousness, private self-consciousness (self-reflectiveness and internal state awareness), and two emotion-regulation strategies: cognitive reappraisal and expressive suppression. 59 employees of a public hospital completed a survey. Public self-consciousness was not associated with either emotion-regulation strategy, while both dimensions of private self-consciousness were related to the strategies. While self-reflectiveness was correlated with expressive suppression, internal states awareness was associated with cognitive reappraisal.